The Relationship between Government Regulation and Customer Repurchase Intention on Online Ride Sharing Companies in Bandung 2020 - Azizi, Yusuf; Dhewanto, Wawan (Journal of Business and Management, 2020)
Abstract. On May 2019, the government issues regulation about online ride hailing which can increase the service standard and increase the tariff but in the other hand also give bad impact on decreasing the industry's demand. Based on some literature the good service quality and good perceived price pricing tariff could increase repurchase intention. If the service quality and perceived price are bad, it can makes bad customer satisfaction and also customer loyalty which lead the customer to not repurchase in the industry. It is important to know the correlation of government regulation implementation towards customer satisfaction, customer loyalty, and also repurchase intention. SEM-PLS has been applied in this research to know the correlation of each variables and also the researcher conduct SERVQUAL analysis to know the SERVQUAL gap which will be used to give suggestion regarding the service quality. The data has been collected through questionnaire and get 425 respondents. Gojek’s SEM-PLS result are there is indirect effect of perceived service quality towards repurchase intention through customer satisfaction and customer loyalty, and there is indirect effect of perceived price towards the repurchase intention through customer satisfaction. While for Grab’s SEM-PLS result are there is indirect effect of perceived service quality towards the repurchase intention through customer satisfaction, and there is significance influence of perceived price towards repurchase intention and also there is indirect effect of perceived price towards repurchase intention through customer satisfaction. In order to increase their perceived service quality both companies are suggested to follow the SERVQUAL analysis result. It is important to maintain good perceived service quality which can lead to repurchase intention.Keywords: Grab, Gojek, Government Regulation, PM No 12 of 2019, KP 348 2019, Perceived Service Quality, Perceived Price, Customer Satisfaction, Customer Loyalty, Repurchase Intention.